ANALYSIS OF WORK LOADS AND PERCEPTION OF LEADERSHIP STYLE ON NURSING PERFORMANCE IN PUSKESMAS NGANTRU TULUNGAGUNG DISTRICT - Saputra, Deva Arif; Amarin yudhana; Prima Dewi K. (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
The performance of nurses at the puskesmas plays an important role in determining the back and forth of the organization. High workloads and ineffective leadership styles can interfere with nurse performance. The purpose of this study was to determine the relationship of workload and leadership style to the performance of inpatient nurses in the Ngantru health center, Tulungagung Regency. The design of this study was quantitative research using a cross sectional approach with a population of 31 nurses in Ngantru Public Health Center, Tulungagung Regency. The sample is all of the population with a total sampling sampling technique of 31 respondents. The collected data is processed by ordinal regression statistical tests. with significance α = 0.05. The results showed that from 31 respondents, most of the respondents had a moderate workload, namely 20 respondents (64.5%), most of the respondents stated that the leadership style of the leader was democratic, namely 18 respondents (58.1%) and some the number of respondents has sufficient performance, namely 16 respondents (51.6%). The results of the ordinal regression test show that the value of p-value = 0.002 (<0.05) in the leadership style factor which means reject H0 and accept H1 so that there is a relationship between leadership style and nurse performance. It is necessary to strive for effective HR arrangements to avoid workloads and excessive work fluctuations that have an impact on the emergence of saturation and boredom of work which results in performance.